La gran porotada Recetas e historias del poroto en Chile - Belmar, Carolina; Jara, Natalia; Baginsky, Cecilia; Meisel, Lee (Social-ediciones, 2023)
The book, created by a team of scientists from various disciplines, culinary professionals, and with the contribution of recipes collected through an open contest, represents an exploration of the historical, cultural, and nutritional role of one of the most iconic ingredients in Chilean gastronomy: the bean. The book covers both the richness of culinary and social traditions related to beans as well as their significance in health and agriculture.